Synergistic Zinc Molybdate-Carbon Nanosphere Nanocomposites for Enhanced Electrochemical Performance and Efficient Photocatalytic Applications - Radhalayam, D (Elsevier Ltd, 2025)
Transition metal molybdates such as zinc molybdate have gained considerable attention for applications to energy storage systems, namely in lithium-ion batteries (LIBs), and for environmental remediation, particularly in the photocatalytic degradation of organic pollutants. However, practical applications of these materials are hindered by their intrinsically poor electronic conductivities and suboptimal ion-transport kinetics. This study aimed to address these limitations by synthesizing a zinc molybdate-carbon nanosphere (ZMO@CNS) nanocomposite using a facile hydrothermal method. The synthesized nanocomposites were extensively characterized using various analytical techniques. An electrochemical evaluation revealed that the ZMO@CNS anode exhibited an impressive initial discharge capacity of 1933 mAh g−1 at a current density of 1 A g−1 and retained a high capacity of 1185 mAh g−1 after rapid discharge cycles. Further, it maintained a discharge capacity of 975 mAh g−1 after 500 cycles, demonstrating excellent cycling stability. Photocatalytic assessments showed that, within 100 min, ZMO@CNS degraded 99 % of crystal violet, which is a representative organic contaminant, in an aqueous solution. These findings highlight the dual functionality of the ZMO@CNS nanocomposite as a high-performance anode material for LIBs and as an efficient photocatalyst, making it a candidate for sustainable and multifaceted technological applications. © 2025 Elsevier B.V.